2022
DOI: 10.3390/foods11203256
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Current State and Future Prospects in Resource Recovery of Chinese Cereal Vinegar Residue

Abstract: Vinegar residue (VR) is a typical organic solid waste in Chinese cereal vinegar production. It is characterized by high yield, high moisture and low pH and is rich in lignocellulose and other organic matter. To avoid the environmental pollution caused by VR, it should be properly treated. The industry’s existing treatment processes, landfills and incineration, cause secondary pollution and waste of resources. Therefore, there is an urgent demand for environmentally friendly and cost-effective resource recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Similarly, it was observed that direct feeding of vinegar residue to pigs could lead to multiple problems such as constipation, discomfort, and indigestion (Jiang, 2008). However, fermenting vinegar residue with the aid of specific microbial strains was shown to effectively increase its nutrient content (Wang et al, 2022a). The present study indicated that the addition of 4.5% urea and 15% wheat bran to the fermenting mixture significantly increased the crude protein content compared to the control group.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Similarly, it was observed that direct feeding of vinegar residue to pigs could lead to multiple problems such as constipation, discomfort, and indigestion (Jiang, 2008). However, fermenting vinegar residue with the aid of specific microbial strains was shown to effectively increase its nutrient content (Wang et al, 2022a). The present study indicated that the addition of 4.5% urea and 15% wheat bran to the fermenting mixture significantly increased the crude protein content compared to the control group.…”
Section: Discussionmentioning
confidence: 50%
“…Proper disposal of vinegar residue is crucial to prevent any adverse environmental impacts. Vinegar residue contains specific nutritional components, such as nitrogen-free extract, crude protein, and short-chain fatty acids, making it a potential feed ingredient (Wang et al, 2022a). However, the content of these components is insufficient to be fed directly to animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation